Teknik Self-Instruction Dalam Mengurangi Stres Akademik Pada Mahasiswa Bimbingan Dan Konseling - Ririanti Rachamayanie; Muhammad Andri Setiawan; Ahmad Samarul Fuadi (JURNAL KONSELING GUSJIGANG, 2018)
Academic stress is a student response to academic demands of learning science with biological, psychological, and social resources (perceived as material beyond the limits of ability) characterized by various reactions that affect the physical, emotional, mental and behavioral. One technique to assist students in reducing academic stress is to use Self-Instruction counseling techniques. The purpose of this research is to know the description of academic stress level of students before and after being given counseling with Self-Instruction approach, and to know the effectiveness of this counseling technique in reducing academic stress on student Guidance Counseling 2013 FKIP Unlam Banjarmasin. This research is a quantitative research using experimental method with pre-experimental designs design, using intact-group comparison. This research was conducted in Guidance and Counseling Program of FKIP Unlam Banjarmasin. Based on the results of data analysis techniques using the t-test formula found there are differences in student's academic stress level before being given counseling using Self Intructions techniques and after being given counseling. Based on the results of the research that has been implemented, it is necessary to note the use of guidelines of the next approach Instructor Self Intructions and study programs. As for the case is this research is still subjective because in the process of individual counseling or the implementation of this experiment, researchers also act as counselors.